1997
DOI: 10.3354/meps154241
|View full text |Cite
|
Sign up to set email alerts
|

Particle capture and deposition by deep-sea sponges from the Norwegian-Greenland Sea

Abstract: Particle uptake and deposition by the 2 most abundant deep-sea demosponge species from the Nolwegian and Greenland Sea (Thenea abyssorum) and the deep fjords of western Norway (Thenea muncata) were studied In flume expenments Fluorescent part~cles of 1, 2, 3 6 10 a n d 16 p m diameter (miclospheres, Duke S c i e n t~f~c Corporat1ono) with a density of 1 0 5 g cm were used at 2 curlent velocities, 1 5 and 5 cm s ' Both species ingested small particles exclusively ( < 6 pm and < l 0 pm, respectively) w~t h a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 24 publications
3
57
0
Order By: Relevance
“…cellulose and siliceous walls), with these cells requiring longer exposure to digestive enzymes (Reiswig 197 1). Several previous studies have reported the ability of sponges to capture diatoms (Reiswig 1971, Frost 1981, Simpson 1984, Witte et al 1997). However, knowledge of their importance as a food source is still Limited.…”
Section: Resultsmentioning
confidence: 99%
“…cellulose and siliceous walls), with these cells requiring longer exposure to digestive enzymes (Reiswig 197 1). Several previous studies have reported the ability of sponges to capture diatoms (Reiswig 1971, Frost 1981, Simpson 1984, Witte et al 1997). However, knowledge of their importance as a food source is still Limited.…”
Section: Resultsmentioning
confidence: 99%
“…3C). A potential mechanism for this pattern may be the selective consumption of the larger HDNA bacteria (Gasol et al 1999) by benthic filter-feeding organisms on the reef (Reiswig 1971, Sorokin 1973, Wilkinson et al 1984, Witte et al 1997.…”
Section: Bulk Patternsmentioning
confidence: 99%
“…Whereas the nutritional ecology of shallow suspension feeders has been well studied, equivalent studies of the nutritional ecology of deep-dwelling suspension feeders (below scuba depth) are scarce (Roberts and Hirshfield 2004) and rely largely on descriptive anatomy and in vitro experiments (e.g., Fiala-Medioni et al 1986;Witte et al 1997; Pile and Young 1999 …”
Section: Introductionmentioning
confidence: 99%
“…The feeding activity of these animals can control the water column properties in shallow bays (Cloern 1982), rivers (Strayer et al 1999), and fjords (Riisgå rd 1998), either directly (through grazing on the plankton community) or indirectly (by intensifying nutrient recycling or by selective removal of a specific planktonic component) (Thorp and Casper 2003). These activities are tightly coupled with hydrodynamic processes.Whereas the nutritional ecology of shallow suspension feeders has been well studied, equivalent studies of the nutritional ecology of deep-dwelling suspension feeders (below scuba depth) are scarce (Roberts and Hirshfield 2004) and rely largely on descriptive anatomy and in vitro experiments (e.g., Fiala-Medioni et al 1986;Witte et al 1997; Pile and Young 1999 …”
mentioning
confidence: 99%